Skills of future workforce: skills gap based on perspectives from academicians and industry players - Noor Nazihah Mohd Noor; Shazaitul Azreen Rodzalan; Nor Hazana Abdullah; Maisarah Mohamed Saat; Aniza Othman; Harcharanjit Singh (Institute of Advanced Engineering and Science, 2024)
Apart from having specific knowledge, graduates are expected to possess a set of soft and hard skills to be employed. This study aims to identify soft and hard skills relevant to the future workforce in the electrical and electronic (E&E) industry based on two perspectives; academicians from public higher education institution (HEI) and E&E industry players. Further, the study aims to investigate skills gaps between two stakeholders. A total of 50 academicians and 31 industry players in Malaysia were surveyed using a structured questionnaire. Statistical analysis was performed using an independent t-test. In terms of soft skills, analytical thinking skills, communication skills, and discipline were more perceived by academicians, whereas decision-making skills, teamwork skills, and discipline were more favored by industry players. For hard skills, both players favored technology use, except for organizational capabilities which were perceived more by academicians while troubleshooting was favored more by industry players. This study contributes to the collaboration between public HEI and the E&E industry to address the skills gaps, which will benefit all stakeholders. This study focuses on the skills that are perceived more by both stakeholders.